Numerical Simulation of Reinforced Concrete Mine Seal Subjected to Explosion Loading - Khaled Morsy (International Conference on Ground Control in Mining, 2008)
The tragic incidents at Sago and Darby coal mines in 2006 pointed out the need for stronger seals to resist the blast effects of violent gob explosions. Mine Safety and Health Administration (MSHA) has published the final rule on Sealing of Abandoned Areas in April 2008. According to the final rule, the mine seals for unmonitored gob areas should withstand an instantaneous pressure of 120 psi. Reinforced concrete (RC) seal is one of the feasible options that can be used to meet the final rule. Concrete is a heterogeneous, cohesive-frictional material and exhibits complex non-linear inelastic behavior under multi-axial state of stress. The increased use of concrete as primary structural material requires the development of sophisticated material models to have an accurate prediction of the material response to a variety of loading situations. The constitutive modeling of concrete has advanced considerably in the past three decades. Choosing a reasonable concrete material model is important in order to obtain an accurate mine seal design. This paper attempts to address the effect of different concrete material models on the response of RC seal subjected to dynamic loads from methane explosion. Three concrete models, from ABAQUS library, were selected to address the effect of non-linear behavior of concrete and damages due to tensile and compressive stresses. In addition, a typical and verified concrete material model was used for conducting 3D finite element models simulating the RC seal by ABAQUS, EXPLICIT ver. 6.6.